PEMANFAATAN CORPORATE SOCIAL RESPONSIBILITY (CSR) BAGI PENINGKATAN KUALITAS HIDUP MANUSIA INDONESIA - Astri, Herlina (Pusat Analisis Keparlemenan Badan Keahlian Sekretariat Jenderal DPR RI, 2012)
Implementation of Corporate Social Responsibility (CSR) in Indonesia should adapt to local situation and characteristics of the human being. This paper aimsat elaborating the implementation and benefits of CSR in Indonesia. The writing process was conducted by consulting a number of sources to draw conclusions. The results show that the realization of CSR to its surrounding community can be done through a variety of community development programs. It is a new way to frame sustainable benefits of CSR to society maximizing building potential.